Indications of admitting patients in internal ICU and the rate of mortality in Emam Khomeini hospital in 2013 - Ghobadi, Hasan; Habibzadeh, Shahram; Shahbazzadegan, Bita; Mirzanezhadasl, Mohsen; Kamranimoghaddam, Mahsa (International Journal Of Community Medicine And Public Health, 2019)
Background: ICU is the costly part of the hospital that has functional approach for patients who have reversible conditions so it needs mechanical ventilation and other special services. Some patients are not really in need of special care only the continuous monitoring of vital signs needs of the public sector. Patients with good condition or End-Stage were not candidate to admitting in ICU. The aim of this study was to evaluate indications of admitting patients in internal ICU and the rate of mortality in Emam Khomeini hospital in 2013. Methods: The study was conducted retrospectively evaluated the records of patients hospitalized in ICU and disease prognosis and treatment of disease and APACHE2 criteria was analyses. Results: The mean age of patients in the study was 61.05±19.81. Of 118 patients, 70 (59.3%) survived and 48 (40.7%) patients died. APACHE2 mean in the study was 21.46±7.5. GCS average was 9.83±4.27. There was correlation between mortality of patients and type of disease. In this study in APACHE2 score between 25-29 and >35 in mortality rate we are higher than standard average and in 10-14 and 20-24 we are lower than standard average. Conclusions: This study shows that GCS is not a good measure for the evaluation of patients hospitalized in internal ICU. In the present study, patients with higher APACHE2 score of 35 died. That show hospitalization that patient in ICU has no difference in the prognosis of them. As regards mortality rate in ICU patients in this study has no significant difference with predicted APACHE values, indications of ICU admition in Emam Khomeini hospital observed exactly.